Essential Service Products as Channels for COVID-19 Awareness and Behavior Change: A Narrative Review - Pathak, Vineet Kumar; P., Karpaga Priya; Panigrahi, Sunil Kumar; Raj, Utsav; Kumar, Mohan (Annals of the National Academy of Medical Sciences (India), 2023)
Coronavirus disease 2019 (COVID-19) is here to stay. Nonpharmacological interventions such as hand hygiene, social distancing, and respiratory hygiene have remained the mainstay to curb the spread of the virus, and these are sustainable. To understand the information, education, and communication (IEC) efforts undertaken during previous pandemics and successful behavior change strategies that may be applicable to ongoing COVID-19 pandemic, we conducted a narrative review of articles using PubMed search on September 11, 2022. The results highlighted that reinforced IEC is the need of the hour in efforts against COVID-19 pandemic. The communication strategy during a pandemic should be of three stages aligned to the objectives of building a basic understanding and knowledge in the target population: building an awareness of the threat; personal actions to minimize the impact; and reinforcing the need for appropriate actions to minimize disease transmission, in that order. An innovative strategy of displaying IEC on the daily essential products can result in a sustainable solution that might result in a “felt need” in the community to follow COVID-19 appropriate behavior. A broad base of stakeholders' engagement with civil bodies, nongovernmental organizations, private sectors with well-defined responsibilities and accountability would offer an enabling environment for these efforts in ultimately curbing the COVID-19 pandemic.
Keywords: COVID-19; essential service products; behavior change; narrative review